(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Context: Accidents are considered as one of the major causes of death in present scenario with head injuries being the most serious in terms of morbidity and mortality. Primary damage triggered at moment of injury results in scalp laceration, skull fractures, contusion, laceration of brain, intra cranial hemorrhage and diffused axonal injury. Road traffic injuries are among one of the six leading causes of death in the age range of15 to 60 years in all countries of South East Asia region. The alarming increase in morbidity and mortality over past few decades associated with road traffic accidents is a matter of great concern globally.